(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Mastitis is the most common and costly dairy cow disease worldwide. We performed an intensive analysis of mastitis prevalence, pathogens, and treatments using retrospective data from a commercial dairy farm in Germany to estimate the severity of mastitis in the commercial production system and to give on-farm insights. Material and Methods: Milking system data and cow-individual data were collected over 9 years (2012-2021). A resilient amount of data from 1537 cows, >1,000 mastitis infections, 1901 pathogens, and 5729 treatments have been analyzed. Results: Mastitis occurrence was highest in summer (45.0%), in first lactation (51.1%), and in the late lactation stage (36.7%). The relative mastitis frequency increased sharply with a high lactation number (>7). The leading pathogens causing mastitis were coagulase-negative staphylococci (28.3%). Approximately 25% of mastitis cases were treated with non-antibiotic medicine and 75% with antibiotics. For the latter, cephalosporins and aminoglycosides were the most administered. The average mastitis treatment duration was 3.48 days. During the study time, the farm changed from a conventional milking system to an automatic milking system in 2015, which has not negatively affected the number of recorded mastitis infections. Conclusion: This case report gives detailed insights about mastitis incidences gained under practical conditions. Novel information about mastitis drug usage and duration is presented. Potential mastitis risk factors identified from the results of this study were the summer season, first or >7 lactation(s), and the late lactation stage. J. Adv. Vet. Anim. Res., 11(4): 856–868, December 2024 http://doi.org/10.5455/javar.2024.k837